As infraestruturas de pesquisa no Brasil e o perfil de financiamento da FINEP - Silva, Luciana Bittencourt da (2017)
The main objective of this study is to characterize the country's research infrastructures and to analyze the financing contribution of Finep to the construction of a modern and competitive research infrastructure. To achieve this objective, the database of the national mapping of the national infrastructures carried out by the IPEA (2016) was used, which contains information on 1.760 research infrastructures in the country, of which 238 reported receiving financial support from Finep. In this sense, the sample was divided in two categories - infrastructures financed by Finep and infrastructures not financed by Finep - to describe the frequency of occurrence as to its central tendency, mainly the average, of the following variables: economic aspects, general conditions, activities developed and scientific production of research infrastructures. Based on the analysis of the infrastructure, the following results could be presented: (i) Finep has supported the infrastructure of higher value and has larger equipment; (ii) the infrastructures financed by Finep are more modern and advanced - compared to the best infrastructures in the country and also those observed abroad; (iii) the infrastructure financed by Finep shows a higher percentage of cooperation with companies, national and international institutions, and also a higher percentage of technology and business services, and (iv) the average number of articles produced in infrastructure financed by Finep is about 20% higher than in infrastructures not financed by Finep. One of the limitations of the study is the difficulty in specifying the monetary values of the main sources of financing of the infrastructures, so it was considered as proxy if the infrastructure had received resources from Finep or not and, we characterized the infrastructure as "with Finep support" and "without Finep support". Another point relates to the temporal aspect, since the survey was fixed in a certain period, more precisely, in the year 2012, so that similar studies can be developed at another time with the same sample and achieve different results. Finally, it is worth mentioning the limitation of this study regarding the analyzed sample, which may present selection bias, endogeny and causality. This study aimed to analyze the country's research infrastructures in the context of the National System of Innovation and the contribution of Finep to its strengthening, given the intrinsic need to have results that offer society information on the return of the public investments applied by Finep in the country's research infrastructures.